Eksistensi Upacara Ngekeb, Di Desa Mengwi Kecamatan Mengwi, Kabupaten Badung - I Made Gami Sandi Untara (Pramana: Jurnal Hasil Penelitian, 2021)
One of the religious ceremonies belonging to the Manusa yaja ceremony is the Ngekeb ceremony which is contained in the procession of the Metatah ceremony / tooth cutting. The Ngekeb ceremony means to bring humans closer to their natural environment, to each other and to God. The Ngekeb ceremony is carried out in a room or in a gedong. During the procession of the Ngekeb ceremony someone who carries out this ceremony is not allowed to leave the room or gedong. The forms of implementation of the Ngekeb Ceremony are: 1) Upakara facilities at the Ngekeb Ceremony using banten pejati, byakala and prayascita 2) The procession of the Ngekeb Ceremony starting from the initial stage, the core stage to the final stage of the Ngekeb Ceremony 3) The time of the Ngekeb ceremony being carried out the day before the ceremony mepandes 4) The clothes at the Ngekeb Ceremony are middle traditional clothes 5) The Pamuput at the Ngekeb Ceremony is a Stakeholder. Functions of the Ngekeb Ceremony a) Control function to be able to control thoughts, words and actions b) Religious function is seen when the holder leads prayers using offerings or Nyekeb ceremony facilities. Social can be seen when the cohesiveness of the community in the implementation of the Ngekeb Ceremony. In the Ngekeb ceremony it has meanings, namely: a) Symbolic meaning, namely through the means used in the Nyekeb ceremony in the form of an upakara or offering b) Philosophical meaning in the Ngekeb Ceremony Implementation This Ngekeb ceremony is the creation of nature that begins with darkness, then gets light and the creation process occurs. . c) The meaning of ethics at the Ngekeb Ceremony is contained in the behavior of the people who are very obedient to their own sanctity, besides that the Ngekeb ceremony is held to provide character education in the form of advice as spiritual guidelines for children.